From cave to cloud : media and information literacy for today - Campos, Patrick F. (Quezon, City : Phoenix Publishing House, Inc., 2016)
"From Cave to Cloud provides today's learners with a vital educational resource for developing media and information literacy as a personal and social pursuit. As an educational resource, the book offers a historical survey of the evolution of media and information technologies and traces how these technologies, in turn, have shaped and continue to influence history".
Includes endnotes.
English text.
Keywords: Mass media